Design Criteria for Pocket Parks in Old City Districts: Fostering Shared Urban Landscapes - Han , Dong; Mamat , Mohd Jaki Bin (International Journal of Basic and Applied Sciences, 2025)
Pocket parks have become essential tools for improving social interaction, environmental quality, and public well-being because of China’s fast urbanisation, especially in crowded old metropolitan areas. Underutilisation and inefficient land use result from the planning and design of these small-scale green spaces, which frequently lack scientific quality. Using a mixed-methods approach that incorporates field observations, geographical analysis, user surveys, and expert interviews, this study examines 70 pocket parks in Taiyuan, Shanxi Province, China. The results show that the park’s location, design elements, and community demands are not aligned, underscoring the significance of functional coordination, cultural readability, and perceptual clarity. This research offers a set of evidence-based design and siting criteria for pocket parks in historic urban settings by including the shared urban landscapes principles, which prioritise usability, accessibility, and social inclusion. The findings encourage inclusive and resilient cityscapes and promote sustainable, human-centered urban regeneration by offering practical insights to policymakers, landscape architects, and urban planners.